IMPLEMENTASI TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN INFORMATION SYSTEMS SUCCESS MODEL (ISSM) DALAM MENGUKUR EFEKTIFITAS PENGGUNAAN SISTEM INFORMASI SIKADUKU UNIVERSITAS KUNINGAN: STUDI KASUS PENGGUNA SIKADUKU DI LINGKUNGAN UNIVERSITAS KUNINGAN - Rio Priantama (Sistem Informasi Fakultas Ilmu Komputer Universitas Kuningan, 2018)
Integrated Academic Information System of Kuningan University (SIKADUKU) is an integrated academic information system built and developed in Kuningan University as a strategic step in organizational management. UNIKU as an organization needs to pay attention to the existence of factors that can influence effectiveness of the use of Information System so that the occurrence of